Abstinence and current or former alcohol use as predictors of disability retirement in Finland. Issue 4 (June 2015) - Kaila-Kangas, Leena; Kivekäs, Teija; Laitinen, Jaana; Koskinen, Aki; Härkänen, Tommi; Hirvonen, Leena; Leino-Arjas, Päivi
Aim : According to previous studies, abstinence from alcohol increases the risk of disability retirement (DR). We studied whether former alcohol users' poor mental or physical health might have contributed to this result. Methods : Prospective population-based study of 3621 occupationally active Finns aged 30–55 years at baseline. Disability pension data for 2000−2011 was retrieved from national pension records. We examined medically certified disability retirement due to all causes and due to mental disorders among lifelong abstainers, former drinkers, those with an alcohol use disorder irrespective of consumption and current users, further classified according to weekly intake of alcohol. Chronic somatic diseases were evaluated in a clinical examination and common mental and alcohol use disorders using the Composite International Diagnostic Interview. Cox regression was used. Results : Neither lifelong abstinence nor alcohol consumption, even at hazardous levels, without alcohol use disorder was associated with disability retirement. Compared with light drinkers, former drinkers' hazard ratio for DR due to mental disorders was 2.67 (95% CI 1.39−5.13), allowing for somatic and mental morbidity, physical and psychosocial workload, health behaviour and socio-demographic factors. The respective hazard ratio of DR due to all causes for those with alcohol use disorder was 2.17 (1.49−3.16) and of DR due to mental disorders 4.04 (2.02 to 8.06). Conclusions : Lifelong abstinence did not predict disability retirement. Former drinkers and people with alcohol use disorders were at a multi-fold risk of work disability due to mental disorders compared with light drinkers, thus it is important to support their work ability.